Conversion of ER, PR, HER2 and Ki-67 and Prognosis in breast cancer metastases to the brain - Chen Jiaxin; Zhou Jinmei; Zhang Huiqiang; Wu Xuexue; Wang Xiaobo; Zhang Shaohua; Tai Yanhong; Jiang Zefei; Wang Tao; Wang Tao; Wang Tao (Frontiers in Neurology, 2022)
ObjectiveThis study aimed to analyze the expression levels of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2), and Ki-67 proliferation index in the brain metastatic lesions and primary lesions in Chinese patients with breast cancer brain metastasis (BCBM) and determine the correlation between their changes and patients' survival.MethodsA retrospective analysis was performed on patients with BCBM. The clinical characteristic of these patients was collected. The differences in the expression levels of the ER, PR, HER-2, and Ki-67 index between the primary lesions and brain lesions were evaluated, and the association between the differences and survival was analyzed.ResultsThe conversion rate of anyone receptor (ER, PR, or HER2) between the primary lesions and brain metastatic lesions was 45.0% (18/40), of which the ER inconsistency rate was 25.0%, the PR inconsistency rate was 22.5%, and the HER-2 inconsistency rate was 15.0%, and the receptor conversion resulted in a subtype conversion of 27.5% (11/40). The patients with HER-2 expression discordance between the primary lesions and the brain metastatic lesions had significantly longer survival times (58.9 vs. 26.4 months, P = 0.04) after diagnosis of brain metastases.ConclusionIn this study, 45.0% of breast cancer patients developed biomarker-conversion between the primary lesions and brain metastatic lesions, and the differences in the expression levels of the ER, PR, and HER-2, the change in Ki-67 index between the primary lesions and brain lesions may predict patients' survival.